Enhancing students’ digital literacy at EFL classroom: Strategies of teachers and school administrators - Hussien Mohamad Razak; Norizan Abdul Razak; Pramela Krish (LPMPP Universitas Negeri Yogyakarta, 2022)
Promoting digital literacies is the apparent goal of an extensive array of educational initiatives in all educational contexts. However, very limited attention has been directed toward the strategies of promoting students’ digital literacies in the literature. Thus, this qualitative study aims to identify the strategies of EFL teachers and school administrators in promoting EFL students’ digital literacies to thrive in the new normal challenges. Semi-structured interviews with 6 EFL teachers and 6 school admins from the Arab international schools in Kuala Lumpur were gathered using a convenient sampling technique. The qualitative data were analysed and reported thematically. The findings of the study revealed that teachers reported four strategies to promote students’ digital literacy: motivating students, conducting training workshops, actual use of digital technologies in the classroom, and enhancing classroom digital infrastructure. Similarly, school admins reported four strategies: rising parents’ awareness towards the importance of digital technologies, training teachers and students, enhancing classroom infrastructure and redesigning the EFL classroom. These findings offer implications for policymakers and researchers, especially those interested in enhancing students’ digital literacies. The results require further urgent large-scale investigations to address the factors that currently constrain the promotion of digital technologies.